Nanoliposomes as a vehicle for Omega-3 delivery in yoghurts: a mice study - Diaz, Gabriela Esther; Foltran, Rocío Beatriz; Diaz, Silvina Laura; Feliu, María Susana; Impa Condori, Anabel Rocío; Guidi, Silvina Mabel; Ambrosi, Vanina; Nanni, Mariana; Pega, Juan Franco; Godoy, Maria Fernanda (Ministerio de Producción, Ciencia e Innovación Tecnológica, Córdoba, 2026)
Poster